DETERMINANTS OF EATING HABITS AND PHYSICAL ACTIVITY AMONG FEMALE STUDENTS OF GOVERNMENT SCHOOLS OF URBAN CITY OF PAKISTAN - Javaid, Fasiha; Sheerani, Nand Lal; Haider, Shagfta; Anwar, Fozia; Azad, Maria; Kumari, Priyanka; Kanwal, Saira; Kumar, Ramesh (Journal of Ayub Medical College Abbottabad, 2020)
Background: Obesity is constantly increasing among adolescents since the last few decades becoming an alarming situation worldwide. The objective of this study was to know the determinants of eating habits and physical activities among school-going female adolescents of public sectors schools of Rawalpindi Pakistan. Methods: A cross sectional study with mixed method with both quantitative and qualitative approach was conducted on three public sector schools of Rawalpindi Pakistan. Sample size of 384 female students of grade 5-10 were interviewed on reliable and validated tool after taking their consent and ethically approval. Moreover, four focus group discussion (FGD) with 30-45 minutes spent on each were conducted by inviting 6-8 participants in each group. Qualitative findings were triangulated with quantitative results. Study was ethically approved from the institutional review board of Health Services Academy Islamabad Pakistan. Results: Females schools' students were included in this study were 384 with mean (SD) age 11.9±1 year. Majority (38%) were of class 7th and their mothers (42%) were educated. Mostly (42%) students were obese (53%) eat the vegetables rarely in their diet. Above half (59%) were those students who eat deep fried potato chips daily. There was a significance difference were seen among normal and obese female students regarding the dietary habits in different class of enrolment (<0.001), mother's education (0.04), intake of sweat confectionary (0.01), intake of meat (0.00), junk food (0.00), use of energy drink (0.03), use of milk (0.02), physical activity (0.00) and play games (0.00). However, intake of vegetables (0.23) and mother's education (0.081) were found insignificant in this study. Majority (88.5%) of students were also playing games in their daily activity. Below half (44%) respondents used to involve in physical activity. Qualitative findings triangulate with quantitative findings and themes were generated like;awareness on healthy diet, eating junk food, dislikes vegetables in diet and physical activity. Conclusion: Study concluded the factors including student's age, mother's education, intake of junk food, physical activity and play games are associated with obesity among the female students of government school in urban area of the country. Keywords: Eating habits; determinants; physical activity; Female students; adolescent; active games and exercise